The life and work of Anna Danielová with regard to her professional career in UGR, namely in the Commission of former CC prisoners and in the Commision of women - Závodská, Milada (Romano džaniben, 2025)
The article focuses on the historical personality of Anna Danielová (1921–1999). Based on archival research, it examines the prerequisites that the talented student applied first in her education and later in her professional career. A graduate of a business academy, she was employed in the civil service as an accountant and also as a personnel officer. The article explores the exceptional strength of Danielová’s personal commitment with which she drew on her professional competencies to improve the quality of life of Romani people in Czechoslovakia. Danielová’s life story is thus interconnected with other personalities among the Romani actors who have repeatedly opened a dialogue with the power structures of Czechoslovakia since the end of World War II. The legacy of Anna Danielová’s life’s work places this woman among the important Romani female personalities in the 20th century.